Decoding the Rabies Phosphoprotein: A First Look at Evolutionary and Structural Dynamics of Rabies Virus in Mumbai, India - Sawant, Gauri R.; Pharande, Rajesh R.; Gandge, Rajashree S.; Thorat, Varsha D.; Ingole, Shailesh D.; Zende, Ravindra J. (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
Rabies remains a significant zoonotic threat in India, where dog-mediated transmission causes substantial human mortality and necessitates robust molecular surveillance. The rabies virus (RABV) phosphoprotein (P) gene is a critical determinant of viral replication, neuro-invasiveness, and host immune evasion. The present study aimed to detect and characterise the full-length P gene from rabies-suspected dog brain samples in Mumbai. RT-PCR demonstrated complete concordance with dFAT, successfully amplifying the full-length 894 bp P gene in 14/20 samples (70%). Automated genotyping and phylogenetic reconstruction of five representative amplicons classified the study sequences within the Arctic-like 1a (AL1a) lineage, clustering distinctly into a localised Peninsular India subclade. Evolutionary pressure analysis indicated strong purifying selection acting on the gene. Deduced amino acid sequence analysis identified 26 non-synonymous mutations across the P protein, including conserved clade-defining mutations E165D and A267G, and novel mutations G54R and A171V. In silico 3D structural modelling of critical domains revealed conserved spatial architecture in comparison to the SAD B19 vaccine strain. The study findings highlight the region-specific evolutionary dynamics, genetic diversity, and structural stability of endemic RABV variants in Mumbai, India.
Keywords: Arctic-like 1a; Phosphoprotein; Phylogeny; Rabies virus; Structural modeling